The complete mitochondrial genome of Hapalogenys analis (Perciformes, Haemulidea) except for control region, obtained by whole genome sequencing. Issue 3 (2nd July 2020) - Zheng, Yunya; Feng, Linxiao; Liu, Haoyu; Song, Riyu; Xu, Shengyong; Shi, Huilai; Gao, Tianxiang
Abstract: In this study, we obtained the complete mitochondrial genome of Hapalogenys analis using whole genome sequencing. With the exception for control region, this mitochondrial genome, consisting of 16, 355 base pairs (bp), contains 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), and 21 transfer RNAs (tRNAs). This mitochondrial genome also lacks a tRNA-Pro gene after tRNA-Thr gene. The overall base composition shows 25.45% of T, 29.73% of C, 28.68% of A and 16.14% of G, with a slight A + T rich feature (54.13%). Sanger sequencing is needed to confirm the accuracy of control region, as well as the lack of tRNA-Pro gene. The mitogenome data provides useful genetic markers for the studies on the molecular identification, population genetics, phylogenetic analysis and conservation genetics.